Studies on economic growth and income in Sub-Saharan Africa - Asiedu, Michael Kwame (2016)
A thesis submitted to The School of Graduate Studies, Kwame Nkrumah University of Science & Technology, Kumasi in fulfilment of the requirements for the award of Doctor of Philosophy in Economics,